2020
DOI: 10.1167/iovs.61.13.37
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Retinal Oscillations by Benzodiazepines Improves Efficiency of Electrical Stimulation in the Mouse Model of RP, rd10

Abstract: In RP, photoreceptors degenerate. Retinal prostheses are considered a suitable strategy to restore vision. In animal models of RP, a pathologic rhythmic activity seems to compromise the efficiency of retinal ganglion cell stimulation by an electrical prosthesis. We, therefore, strove to eliminate this pathologic activity. METHODS. Electrophysiologic recordings of local field potentials and spike activity of retinal ganglion cells were obtained in vitro from retinae of wild-type and rd10 mice using multielectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The first step was to eliminate rhythmic bursts and local field potentials observed in the RD retina. Some studies have shown that the SNR of a single RGC response upon electrical stimulation improves after the application of drugs, such as MFA and benzodiazepines, with the disappearance of abnormal spontaneous activity ( Toychiev et al, 2013 ; Eleftheriou et al, 2017 ; Gehlen et al, 2020 ). Our results, considering the response of the RGC population to electrical stimulation, demonstrated the effectiveness of drug treatment with MFA ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…The first step was to eliminate rhythmic bursts and local field potentials observed in the RD retina. Some studies have shown that the SNR of a single RGC response upon electrical stimulation improves after the application of drugs, such as MFA and benzodiazepines, with the disappearance of abnormal spontaneous activity ( Toychiev et al, 2013 ; Eleftheriou et al, 2017 ; Gehlen et al, 2020 ). Our results, considering the response of the RGC population to electrical stimulation, demonstrated the effectiveness of drug treatment with MFA ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Past work has largely converged on a model where a gap junction coupled excitatory network, gives rise to oscillatory spontaneous activity in the rd10 retina ( Euler and Schubert, 2015 ; Trenholm and Awatramani, 2015 , for review) although, studies indicated that inhibition plays a role in modulating this spontaneous activity ( Margolis and Detwiler, 2011 ; Biswas et al, 2014 ; Gehlen et al, 2020 ). To examine how inhibition modulates or synchronizes spontaneous activity in response to stimulation, we repeated these experiments during inhibitory neurotransmitter block.…”
Section: Resultsmentioning
confidence: 99%
“…Spontaneous activity typically manifests as rhythmic bursting or oscillatory activity. Previous studies, most commonly in the rd1 or rd10 ( Chang et al, 2002 ) mouse models, have shown significant variability in the characteristics of spontaneous activity, such as the dominant frequency, as well as the underlying changes that could mediate this aberrant activity ( Margolis and Detwiler, 2011 ; Biswas et al, 2014 ; Gehlen et al, 2020 ). Putative mechanisms for spontaneous activity can be broadly divided into inner and outer retina mechanisms, which are not mutually exclusive [for review see, Euler and Schubert (2015) and Trenholm and Awatramani (2015) ].…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing ganglion cell activity could, therefore, provide input to V1 even without visual input or functional photoreceptors. Indeed, because of photoreceptor loss, the remaining retina develops aberrant oscillatory activity in mouse models of retinitis pigmentosa ( rd1 and rd10 ) (Margolis et al, 2008 ; Biswas et al, 2014 ; Goo et al, 2016 ; Ivanova et al, 2016 ; Gehlen et al, 2020 ; Ahn et al, 2022 ) and hyperactivity in retinal ganglion cells (Margolis and Detwiler, 2011 ; Stasheff et al, 2011 ; Telias et al, 2019 ; Ahn et al, 2022 ). This aberrant retinal activity develops with the onset of retinal degeneration and is reported for our age group III and beyond, up until 12 months (Stasheff et al, 2011 ; Biswas et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%